Kejadian Penyakit Antraknosa Yang Disebabkan Oleh Colletotrichum sp. Pada Tanaman Cabai Rawit (Capsicum frutescens L.) Di Kecamatan Landasan Ulin Banjarbaru - Luis, Pankrasius Ivan; Liestiany, Elly; Salamiah, Salamiah (www.ulm.ac.id, 2025)
This study aims to examine the incidence of anthracnose disease in chili fruit attacked by the pathogenic fungus Colletotrichum sp. which attacks cayenne pepper plants on agricultural land in Banjarbaru. This research method uses a stratified purposive sampling method. The stratified purposive sampling method is a technique for collecting disease sample data randomly and paying attention to a level or stratification of the population elements to be determined and observed. This research uses a survey research method by taking cases of disease occurrence in cayenne pepper plantations which were attacked by anthracnose pathogens in cayenne pepper farming fields in Landasan Ulin District. The location or location of the observation site was determined by purposive sampling or taking the location deliberately, namely by considering the chili fruit that was harvested infected with anthracnose. On each cayenne pepper planting area, the average total incidence of anthracnose disease on fruit and cayenne pepper plants for 5 consecutive weeks in Guntung Manggis Village had a total percentage of anthracnose disease incidence of 11.15%, while in North Loktabat Village on land cayenne pepper plants with a total disease incidence percentage of 15.59% and in Landasan Ulin Utara Subdistrict Sukamara street with a total incidence percentage on cayenne pepper plantations 4.20% of total disease incidence data.